New Fast Neutron Shielding Material Composing of Alternating Layers of Natural Rubber, SBR and Boron Oxide (B2O3) and Layers of Natural Rubber and Iron(III) Oxide (Fe2O3) - จําปี ชญานิษฐ์; วงศ์แสวง ดุลยพงศ์ (KKU Science Journal, 2016)
Neutrons have been widely used in many applications. Since neutrons have no electric charge, they can travel through electron cloud and directly interact with the atomic nucleus. Exposure to free neutrons can be hazardous especially fast neutrons from neutron source. Therefore, using neutron shielding material is very important. Optimized flexible and lightweight neutron shielding materials were designed using the Monte Carlo N-Particle (MCNP) code. Thicknesses of 10 cm were tested for neutron shielding performances. Simulation results indicated that the shielding material with four alternating layers of NR with 100 phr iron (III) oxide (Fe2O3) and of NR and SBR blend (1:1) with 5 phr boron oxide (B2O3) were most suitable for fast neutron shielding. The neutron shielding material of a spherical shape exhibits the best performance (43% neutron attenuation) compared with cuboid and cylindrical shapes. The optimum neutron shielding material design was fabricated and good homogeneity of the material was verified by neutron radiography. Therefore, this neutron shielding material can be utilized in neutron source applications.